What Happens in-between Mobilizations? Building and Organizing Contentious Politics at the University of Tehran (2007-2017) - Paola Rivetti (Coordinamento SIBA, 2020)
This article investigates contentious politics in authoritarian contexts by looking at the case-study of student activism in the Islamic Republic of Iran. More specifically, the article asks 'how does the Iranian student movement "do" contentious politics?', and argues that a broader approach is needed when examining social movements and mobilizations in authoritarian countries, than one focused on visible mobilizations. In particular, interpersonal relationships, local histories of activism, and what happens 'in-between' episodes of contention should be valued as material carrying analytical gravity. Adopting this approach, the article looks at the continuities and ruptures that have characterized on campus political contention in Iran in the 2000s and 2010s, bringing to the fore the overlooked history of how the student movements have re-organized after major waves of state repression.